Phytonutraceutical composition of dark green, light green, and white varieties of Sechium edule (Jacq.) Sw (Chayote) cooked by different methods from the Vontovorona market, Alakamisy Fenoarivo Commune, in the context of a zero-waste circular economy - Rakotomamonjy Pierre; Ralaibia Boniface Erménégilde; Letsara Rokiman; Razafindrazanakolona Daniel; Rakotomalala Iarivontsoa Nekena Sahaza; Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy (Britain International of Exact Sciences (BIoEx) Journal, 2024)
Three distinct varieties of Sechium edule (dark green, light green, and white) were procured from the Vontovorona open-air market. The chayotes were thoroughly washed and peeled, and their peel, flesh, and seed, whether raw, boiled, or steamed were analyzed for their phytonutraceutical components. Each part was then dried in a dehydrator at 41°C for 48 hours, ground, and placed in sachets. Mineral micronutrient content was assessed using portable X-ray fluorescence equipment, revealing magnesium as the predominant element across all varieties. Specifically, magnesium content in the dark green variety ranged from 1.01% to 2.32%, in the light green variety from 1.13% to 2.32%, and in the white variety from 1.64% to 3.42%. Macronutrient analysis, performed via the Kjeldahl method, indicated moisture content variations in the dark green variety from 84.58% to 90.37%, in the light green variety from 72.87% to 91.74%, and in the white variety from 84.93% to 92.87%. Phytochemical screening identified the presence of flavonols specifically in the raw white variety.